Fluorescence spectroscopy coupled with factorial discriminant analysis as a tool to identify sheep milk from different feeding systems - Hammami M.; Zouari M.; Karoui R.; Rouissi H. (Innovation for sustainability in sheep and goats, 2019)
The present study aimed to determine the potential of Front face fluorescence spectroscopy (FFFS) to discriminate between milk samples from Sicilo-Sarde ewes fed three different diets – named control, faba bean meal and soybean meal - throughout the lactation stage (11 weeks). Milk samples were classified by factorial discriminant analysis (FDA). Similar results were obtained by separately applying (FDA) to different target nutrients (aromatic amino acids and nucleic acids (AAA + NA), tryptophan, vitamin A and riboflavin). In a second step, concatenation technique was applied to FFFS spectra. Results showed a good discrimination between milk samples from different lactation periods and diet compositions. Spectroscopic techniques may provide useful fingerprints, and allow the identification of milk samples from ewes fed different diets throughout the lactation periods.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)